G103(P) Analysis of conjunctivitis management in paediatric emergency department. (27th April 2015) - McCrossan, P; Deiratany, S; Okafor, I; McNamara, R
Abstract : Aims: The aim of this study is to demonstrate an evidence based clinical guideline for the management of conjunctivitis and to illustrate the performance of a paediatric emergency department in its management of presentations of conjunctivitis. Methods: An evidenced based clinical guideline was developed. This guideline was then used as a set standard by which to assess the performance of the emergency department at CUH in its management of conjunctivitis. Data was collected retrospectively. All patients who attended CUH (children's university hospital) diagnosed with conjunctivitis, between 01/06/14–31/08/14 were used for analysis. The emergency department notes for these patients were examined and details of their presentation and subsequent management was noted. These details were collated and compared with the set standard outlined by the new clinical guideline. Results: Mean age at presentation is 5.2 years (SD 1.8) [one month- 15 years]. During the sampled time frame (01/06/14–31/08/14) there were a total of 54 presentations with a discharge diagnosis of conjunctivitis. 86% (25/29) were correctly diagnosed bacterial conjunctivitis. 52% (13/25) were correctly diagnosed allergic conjunctivitis. 30 of the patients had documented features of bacterial conjunctivitis. 40% (12/30) had an eye swabs taken. A total of 13 eye swabs were taken of which only one was indicated. 86% appropriately treated with topical antibiotics. 85% appropriately treated with antihistamines. 7% (3/41) were inappropriately treated with antihistamines. 28% (15/54) were referred for specialist opinion. Discussion: Conjunctivitis is a common presentation to a paediatrics emergency department. Indiscriminate use of microbiological investigations is a significant financial burden to the hospital and one, which can be easily eradicated. Prescribing of topical antibiotics or oral antihistamines should be based on sound clinical grounds so as to avoid unnecessary medicating of patients. Specialist referrals should be well considered.